Politik Hukum Pembentukan Komisi Kebenaran dan Rekonsiliasi Aceh - Khairil Akbar (Lex Renaissance, 2017)
The signing of Memorandum of Understanding in Helsinki between the Free Aceh Movement (GAM) and the Republic of Indonesia (RI) is a sign of peace for the conflict in Aceh. Among the points of agreement is the establishment of the Truth and Reconciliation Commission (KKR) in Aceh. This study aims to investigate and explain the basis for KKR establishment as well as the concept of Aceh KKR. To answer this, the author uses a juridical-normative approach with the library research method. We find that the formation of KKR in Aceh is based on Article 229 of Law No. 11 of 2006 concerning Aceh Government. However, based on the a quo Law, Aceh KKR is referred to as part of National KKR, while National KKR has yet to be established until today. In addition, the institutional concept of Aceh KKR is independent and non-structural with the aim of strengthening peace, helping to achieve reconciliation between perpetrators of human rights violations and victims, and recommending comprehensive reparation for victims of human rights violations. Aceh KKR is based on Islam, Acehnese, independence, impartiality, non-discrimination, democratization, justice and equality, as well as legal certainty.Keywords: Commission; truth; reconciliation; Aceh; human rights